Revitalizing Paper-Based Writing Activities to Enchance Elementary Students’ Literacy Skills in the Digital Era - Magdalena Chori Rahmawati; Pricilla Anindyta; Murniati Agustian; M. Francine Avanti Samino (Jurnal Ilmiah Sekolah Dasar, 2025)
Literacy skills form the foundation of students’ academic and social success, encompassing reading, writing, and comprehension abilities. Handwriting serves not only as a mechanical skill but also as a cognitive and neuromotor process that enhances comprehension, concentration, and memory. This study examines the influence of structured handwriting activities on paper on the literacy skills of 4th- and 5th-grade elementary students. A quantitative quasi-experimental pretest-posttest control group design was employed with 2,293 participants from 53 elementary schools. The experimental group practiced structured handwriting using the Ayo Menulis module, while the control group participated in literacy activities without handwriting emphasis. A literacy test measuring reading, writing, and listening skills was validated by experts and its reliability confirmed through Cronbach’s Alpha. Data were analyzed using parametric (Paired and Independent T-Tests) and non-parametric (Wilcoxon, Mann-Whitney) tests according to data distribution. Results showed that 81% of schools demonstrated significant improvement in literacy skills, and 66% showed significant differences between experimental and control groups. These findings affirm that handwriting-based activities effectively enhance advanced literacy skills and reinforce the cognitive importance of graphomotor processes in learning. The study recommends incorporating handwriting practice into literacy instruction to foster holistic literacy development.